Questioning strategies for effective teaching - Comras, Kevin; Abney, Mark; Instructivision Inc. ([s.l.] : Instructivision Inc., 1997)
Discusses regarding the questioning strategies that every teacher should apply in handling a classroom in order to have an active learning
Title from title screen
Camera, Andy Abbot
Presenter: David Sousa
Keywords: Effective teaching -- United States; Lesson planning -- United States